1998
DOI: 10.1016/s1074-7613(00)80570-1
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins Come of Age: Primitive Functions Acquire New Roles in an Adaptive World

Abstract: Cross-reactive protection was observed in some studies but, with notable exceptions (e.g., Donawho and Kripke, 1990;Frey and Cestari, 1995), such immunity was substantially weaker than the individually specific immunity (Coggin and Anderson, 1974).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
312
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(321 citation statements)
references
References 76 publications
6
312
0
3
Order By: Relevance
“…It has been shown that hsp90 purified from autologous tumours has a protective effect in mouse (Graner et al, 2000;Ullrich et al, 1986). It is now believed that such a protective effect of hsp90 is mainly due to the tumour-derived antigenic peptides that bind to it (Ishii et al, 1999;Srivastava et al, 1998;Wells and Malkovsky, 2000). In our study, since the prokaryotic expression library and purified hsp90 from HeLa cells are unlikely to harbour such antigenic peptides, it seems that the immunoreactivities that we observed are hsp90 specific.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hsp90 purified from autologous tumours has a protective effect in mouse (Graner et al, 2000;Ullrich et al, 1986). It is now believed that such a protective effect of hsp90 is mainly due to the tumour-derived antigenic peptides that bind to it (Ishii et al, 1999;Srivastava et al, 1998;Wells and Malkovsky, 2000). In our study, since the prokaryotic expression library and purified hsp90 from HeLa cells are unlikely to harbour such antigenic peptides, it seems that the immunoreactivities that we observed are hsp90 specific.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent reports have shown the importance of HSPs, such as HSP70, HSP90 and glucose-regulated protein 96 (gp96), in immune reactions. 14,15 HSP-mediated antitumor immunity has been reported in human melanoma and HSP-peptide complexes purified from human melanoma cells induced a vaccine-like effect. 16 With regard to the mechanism of antitumor immunity induced by hyperthermia using MCLs, we previously demonstrated that HSP70 expression during hyperthermia-induced antitumor immunity against the T-9 rat glioma 17,18 ; our hyperthermia system leads to vaccination with HSP70-peptide complexes via necrotic tumor cell death in vivo, thus resulting in antitumor immunity.…”
mentioning
confidence: 99%
“…On the other hand, recent reports have shown the importance of HSPs, such as HSP70, HSP90, and glucose-regulated protein 96 (gp96), in immune reactions. 18,19 A possible mechanism by which HSPs influence tumor cell immunogenicity is associated with the processing and presentation of endogenous tumor antigens directly to tumor-specific T cells. 20 Srivastava and coworkers [21][22][23] proposed the following relay line model for tumor antigenic peptide transfer during antigen processing and presentation by HSPs.…”
mentioning
confidence: 99%